The Overview of Mental Workload of Health Safety and Environment Workers in Oil and Gas Industry - Vica Claudia Fajrin (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: PT. Pertamina RU IV Cilacap is a national oil and gas industry that has the largest refinery in Southeast Asia that manages raw materials for other refinery units in Indonesia to be reprocessed into fuel. The size of the refinery can illustrate the complexity of the system run by this unit. The HSE Unit in this company has a great responsibility to maintain the worker safety in the refinery. It is necessary to measure mental workload on HSE workers. This is because if the mental workload is not monitored, it can cause fatality, in this case, work accidents as a result of lack of supervision from HSE workers and mental PAK related to HSE workers resulting in excessive mental workload or property loss as an outcome of excessive mental workload. So, it is important to portray the HSE mental workload because of its responsibility to secure the health, safety and environmental issues. The purpose of this study was to describe the heavy mental workload on PT. Pertamina RU IV Cilacap. Method: This research was a quantitative descriptive designed study. Data were obtained by conducting interviews and using the NASA-tlx questionnaire on 71 respondents. Results: As many as 35 respondents had heavy mental workloads and 31 respondents had very heavy mental workloads. Conclusion: HSE workers at PT. Pertamina RU IV Cilacap has a heavy mental workload and even tends to be very heavy.Keywords: mental workload, NASA-tlx, oil and gas industry